Comparison of the accuracy of plain radiography and CT scan in diagnosing cervical spineinjuries in trauma patients referred to the emergency department of Imam Hussein (AS)Hospital, Shahroud - Seyedrezaei, Seyedeh Omolbanin; Mahdavi, Sepideh; Abbaszadeh, Maryam; Joukar, Farzaneh; Amiri Largani, Hossein (Shahroud Journal of Medical Sciences, 2025)
Introduction: Trauma is the leading cause of death in developing countries. Head and neck trauma is one of the most common causes of referral to the emergency department following injuries resulting from motor vehicle accidents, sports, fights, and falls from heights. Cervical spine injuries account for 2-3% of trauma patients. This study was conducted to compare the accuracy of plain radiography and CT scan in diagnosing cervical spine injuries in trauma patients in Shahroud city.Materials and Methods: This descriptive-analytical study was conducted using a cross-sectional method and convenient sampling on 115 cervical spine trauma victims referred to the emergency department of Imam Hossein (AS) Hospital in Shahroud in 2018-2019. Data were collected using a demographic information checklist. After collection, the data were entered into SPSS version 23, WinPepi version 11.65, and MEDCALC statistical software and analyzed using descriptive-analytical statistics.Results: In this study, the results showed that out of 115 patients with cervical spine injury, 59.1% were male and 40.9% were female. The mean age of the patients was 39.8 ± 15.3 years. Car accident, rollover and motorcycle accident were the most frequent mechanisms of injury to the patients with 39.1, 24.3 and 20.9% respectively. The sensitivity, specificity, positive and negative predictive value, positive and negative likelihood ratio and area under the Ruck curve for simple radiographs read by an emergency medicine specialist were 55.56, 97.17, 26.5, 96.62, 19.63, 0.46 and 76% respectively. Also, the sensitivity, specificity, positive and negative predictive value, positive and negative likelihood ratio, and area under the Rock curve for plain radiographs read by a radiologist were 0, 0.33, 66.67, 100, 100, 97.25, and 83 percent, respectively.Conclusion: According to the results of the study, it can be stated that plain radiography cannot be considered an appropriate tool to rule out cervical vertebrae injuries caused by trauma. Also, taking radiography may be a waste of time for faster and better diagnosis, as well as a waste of money without achieving appropriate results, given the higher accuracy of CT scanning. Therefore, it is recommended to use CT scanning in case of clinical suspicion or if the radiography images do not meet the standards.